204k views
2 votes
Find the missing factor.
7s^2 + + 13s + 6 = (7s + 6)
)

User Abdi
by
5.7k points

1 Answer

4 votes

Answer:

71s

Explanation:

The question we have at hand is 7s² + ___ + 13s + 6² = (7s + 6)². We can expand the perfect equation " (7s + 6)² " in order to find our solution. A perfect square consists of 3 terms, and hence the term in the blanks must add to 13s to form another term.

Applying the perfect square formula : ( a + b )² = a² + 2ab + b², let's expand the expression,

(7s + 6)² = ( 7s )² + 2( 7s )( 6 ) + ( 6 )² = 7s² + 84s + 6²

84s - 13s = 71s, which fills in the blank provided.

User MoxieandMore
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.